ELECTORAL PROCESSES AND POLITICAL IDENTITIES IN GERMANY AND RUSSIA: ON CONFERENCE MATERIALS - Ashikhmina, Ya.G. (Perm Federal Research Centre Journal, 2015)
This report presents a summary of the results of a scientific conference on electoral practices and political identity in Germany and Russia. The author considers highlights the most discussed questions, identified problems and directions for further research.